PENGARUH SENSE OF HUMOR TERHADAP STRES DIRI PADA MAHASISWA YANG SEDANG MENYUSUN SKRIPSI FAKULTAS PSIKOLOGI UNIVERSITAS SUMATERA UTARA - Sri Ramadhani; Siska Dwi Ningsih; Dwi Nursiti; Agnes Linda Hutabarat (Psikologi Universitas Sari Mutiara Indonesia, 2021)
Thesis is a very crucial thing because the thesis is an indicator of the understanding of the knowledge they apply, because the thesis is a requirement for graduating students from a college so that the thesis is very important to do. The difficulties faced by students in the process of completing the thesis often have a negative impact. Writing a thesis is viewed negatively because it is a tough task for students and it can be stressful. There are many things that can be done to help anticipate and reduce the stress problems faced by students who are preparing their thesis, one of which is a sense of humor. Humor can trigger the laugh reflex, and laughter can also be the best medicine for dealing with stress. This study aims to determine the effect of a sense of humor on self-stress in students who are writing a thesis at the Faculty of Psychology, University of North Sumatra. This is quantitative research is influential. The samples taken in this study were students of the Faculty of Psychology of North Sumatra who were compiling a thesis, so the sample in this study was 83 people. Based on the results of the regression analysis, it shows that the value of the determinant coefficient (R2) is 0.102 and it is explained that the percentage of the influence of the independent variable on the dependent variable is called the coefficient of determination which is the result of squaring R. This means that the sense of humor provides an effective contribution of 10.2% to the self-stress experienced by students who are writing their thesis. While the rest is influenced by other factors not examined. Based on the table above, the significance value of the sense of humor variable (p = 0.000) is smaller than 0.05, meaning this variable has a significant effect on the dependent variable, namely self-stress. It is also found that the regression coefficient is -0.421, the number is negative, so it can be said that sense of humor (X) has a negative effect on self-stress (Y). The calculation results obtained the value of F = 4.881 and p ( Sig). = 0.033. If the p-value < 0.05 then the hypothesis is accepted (Field, 2009). In this study, the p-value (0.033) <0.05, the hypothesis is accepted.